Pengembangan Peta Jalan Menuju Kepatuhan Sertifikasi Halal: Pengabdian Kepada Masyarakat pada Unit Usaha UMKM Bolu di Jadimulya, Pataruman, Banjar - Husaini, Fauzan; Musaddad, Alief Akbar; Afriany, Irna Nur; Eliasari, Susi; Habibah, Tsurroya Azhari (Lembaga Pengabdian kepada Masyarakat (LPkM) Universitas Islam Darussalam (UID) | Islamic University of Darussalam Ciamis-Jawa Barat, 2022)
This research analyzes the challenges faced by Micro, Small, and Medium Enterprises (MSMEs) in achieving compliance with halal certification requirements. As the demand for halal products grows globally, halal certification has become a critical issue in the food and beverage industry. The analysis identifies several key barriers encountered by MSMEs during the certification process, including high costs, limited understanding of certification procedures, and administrative complexities. Additionally, constraints related to production capacity and market access significantly impact MSMEs. Stakeholders—MSMEs, governments, and certification bodies—can use these insights to overcome obstacles and enhance MSMEs’ competitiveness and business sustainability.